PENYULUHANKEWIRAUSAHAAN DAN OPERASIONAL PRODUK - Sahabudin Sidiq (UII, 2013)
Entrepreneurship is an activity that is not foreign in Indonesia. Currently emergingentrepreneurs in Indonesia are generally located in urban areas, one of the mainproblems kewiarusahaan in Indonesia, namely the uneven understanding of theimportance of entrepreneurship for the people living in remote areas. Finally, there isthe economic inequality between urban and rural areas. An understanding ofentrepreneurship need to be inflated in order to raise the economic level of societytowards a better economy. Lots of potential natural resources that can be extracted andcan boost the economy of citizens around but with the lack of knowledge aboutentrepreneurship existing potential is not utilized and not optimized as well as possibleand not occupied thereby earning less than optimal. Therefore it is very necessary toprovide counseling to the local community that there is a potential that can be extractedand utilized by the community. The purpose of this program is increasing citizenknowledge about entrepreneurship and the potential that can be exploited andoptimized in the area where they live. Stagesof entrepreneurship education programs(the importance of innovation in business) is carried out in the post and in homes.Before the survey was carried out in some houses that have natural resources (fruits)which is a lot for sale. After getting fruits,making jams trial began barking, and aftercompletion of the test the jam barked into people's homes. The latter process is todisseminate jam making barking and extension of entrepreneurship (the importance ofinnovation in business). Increased knowledgeof citizens about entrepreneurship and thepotential that can be exploited and optimized in their area, a hope for the author may bebeneficial to the citizens and to improve their economy.